2020
DOI: 10.1016/j.ejogrb.2020.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SARS Cov-2 epidemic on the obstetrical and gynecological emergency service accesses. What happened and what shall we expect now?

Abstract: During the lockdown period, the fear about the risk of infection in hospital has reduced the admission to Emergency Services (ES) with possible negative health effects. We have investigated the changes in the emergency flow occurred during SARS-CoV-2 pandemic in an obstetrics and gynecological ES and the short-term adverse outcomes on women's and reproductive health. Study design: The study was conducted in the OBGYN ES of the Clinica Mangiagalli, the largest maternity clinic of Milan, Lombardy, Northern Italy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
76
1
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(85 citation statements)
references
References 5 publications
5
76
1
3
Order By: Relevance
“…Of 3592 abstracts screened, 192 were relevant for full-text review and 40 met the inclusion criteria for systematic review ( figure 1 ). 4 , 5 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 A list of excluded studies with reasons for exclusion is provided in the appendix (p 6) . Reporting on resource use or service reconfiguration outcomes is summarised in the appendix (p 27) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of 3592 abstracts screened, 192 were relevant for full-text review and 40 met the inclusion criteria for systematic review ( figure 1 ). 4 , 5 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 A list of excluded studies with reasons for exclusion is provided in the appendix (p 6) . Reporting on resource use or service reconfiguration outcomes is summarised in the appendix (p 27) .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 40 included studies, 31 for which comparable outcomes were also reported in at least one other study were included in the meta-analysis. 4 , 12 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 24 , 25 , 26 , 27 , 28 , 30 , 31 , 32 , 33 , 34 , 37 , 38 , 40 , 42 , 45 , 46 , 47 , 48 , 49 Table 1 shows the characteristics of the 40 included studies, all of which used a historical cohort design. 17 countries were represented, with substantial variation in pandemic mitigation measures among countries.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of diagnosing the exact location of the pregnancy, especially in these troublesome times, was highlighted by the latest International Society of Ultrasound in Obstetrics & Gynecology consensus statement [13] . To the best of our knowledge, only one report on the effect of the COVID-19 pandemic on the rate of emergent surgeries due to EUP has been published thus far [14] . That single-center Italian study showed a 20% reduction in EUP-related hospital admission, but it assessed only 16 women in a four-month timeframe.…”
Section: Introductionmentioning
confidence: 99%